Parenting and health in mid-childhood: a longitudinal study. - Waylen A; Stallard N; Stewart-Brown S (European Journal of Public Health, 2008)
BACKGROUND: Parenting and parent-child relationships influence children's emotional and social development and evidence exists that they may be life-course determinants of health. This study tests the hypothesis that adverse parenting in the early years predicts poor health in mid-childhood. METHODS: A prospective study using data from the Avon Longitudinal Study of Parents and Children cohort. Health data on over 8000 children (60% of those recruited) were available for analysis at 6.9 and 7.7 years. Exposures: self-reported maternal hostility, resentment and hitting/shouting in early childhood. Outcomes: maternal report of child's health in general and number of health problems when the child was 6.9 and 7.7 years, adjusting for socioeconomic factors. RESULTS: Sub-optimal parenting, as measured here, was observed among 62, 80 and 83% of families for hostility, resentment and hitting/shouting, respectively. Resentment was more common among older mothers in owner-occupied housing. Resentment and hostility predicted health at both ages independently of socioeconomic circumstances. 'Hitting/shouting' was weakly predictive of number of health problems. A greater proportion of variance was explained by parenting variables than by socio-economic variables. CONCLUSIONS: Parenting and parent-child relationships in the early years predict health in mid-childhood in a way consistent with a causal role. If further studies replicate this finding, policies to improve parenting could be expected to have a modest beneficial impact on health as well as emotional and social development. As some aspects of sub-optimal parenting show reverse social class distribution, initiatives targeted at those living in social deprivation may not achieve the optimum impact on health.